Refusal of Radiation Results in Inferior Survival in Endometrial Cancer. (June 2020) - Parsons, Matthew W.; Francis, Samual; Maurer, Kathryn A.; Grant, Jon; Gaffney, David K.
Abstract : Objective: We sought to understand factors associated with refusal of adjuvant radiotherapy in endometrial cancer and its impact on outcomes. Methods: Data from the National Cancer Database for patients who underwent surgery for nonmetastatic endometrial cancer between 2004 and 2015 were pooled. The Pearson χ 2 test and multivariate logistic regression analyses were used to assess demographic, clinical, and treatment factors. Inverse probability of treatment weighting was used to account for differences in baseline characteristics. Kaplan-Meier analyses and doubly-robust estimation with multivariate Cox proportional hazards modeling were used to analyze overall survival (OS). Results: We identified 4739 of 80, 803 patients (5.9%) who refused radiotherapy. Factors associated with refusal were: no insurance (relative risk [RR]=1.66, P <0.01), Medicare (RR=1.42, P <0.01), living >50 miles from treatment (RR=1.34, P <0.01), Charlson-Deyo Comorbidity Scores of 1 (RR=1.16, P <0.01) or ≥2 RR=1.38, P <0.01), age above 60 years (RR=1.28, P <0.01), International Federation of Gynecology and Obstetrics (FIGO) stages IIIA (RR=1.63, P <0.01) and IIIC (RR=1.65, P <0.01) disease, papillary (RR=1.69, P <0.01) and clear cell histology (RR=1.64, P <0.01). Factors associated with radiation therapy receipt included: Hispanic race (RR=0.61, P <0.01), income >$63, 000 (RR=0.89, P =0.044), undergoing chemotherapy (RR=0.17, P <0.01), FIGO stages IB (RR=0.81, P <0.01) and II (RR=0.70, P <0.01) disease, and lymphadenectomy (RR=0.79, P <0.01). After weighting, 5-year OS was significantly lower with refusal (74.3% vs. 79.7%, P <0.01). This survival decrement was maintained across FIGO stages. Conclusions: We identified characteristics associated with radiation refusal, including socioeconomic barriers, advanced disease stage, and histology. Refusal of radiotherapy conferred decreased OS across FIGO stages. Abstract : Supplemental Digital Content is available in the text.